2002
DOI: 10.1016/s0896-6273(02)00571-8
|View full text |Cite
|
Sign up to set email alerts
|

Feature-Based Anticipation of Cues that Predict Reward in Monkey Caudate Nucleus

Abstract: A subset of caudate neurons fires before cues that instruct the monkey what he should do. To test the hypothesis that the anticipatory activity of such neurons depends on the context of stimulus-reward mapping, we examined their activity while the monkeys performed a memory-guided saccade task in which either the position or the color of a cue indicated presence or absence of reward. Some neurons showed anticipatory activity only when a particular position was associated with reward, while others fired selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(84 citation statements)
references
References 53 publications
(6 reference statements)
4
79
1
Order By: Relevance
“…Recent single-unit recording of neurons in the monkey brain indicates that caudate plays a crucial role in valuation of default actions. Figure 3, adapted from (Lauwereyns, Takikawa et al 2002), provide evidence.…”
Section: Distinguishing Valuation and Choicementioning
confidence: 86%
See 2 more Smart Citations
“…Recent single-unit recording of neurons in the monkey brain indicates that caudate plays a crucial role in valuation of default actions. Figure 3, adapted from (Lauwereyns, Takikawa et al 2002), provide evidence.…”
Section: Distinguishing Valuation and Choicementioning
confidence: 86%
“…In fact, if percentage correct saccades are an indication, effort is involved in avoiding the default action. Indeed, Lauwereyns et al (2002) reports that the monkey makes more mistakes, i.e., moves its eyes in the wrong direction, when the stimulus requires a saccade in the less rewarding direction.…”
Section: Distinguishing Valuation and Choicementioning
confidence: 99%
See 1 more Smart Citation
“…It is also one of several structures in the brain, along with other parts of the basal ganglia and several areas of cortex, that represent the anticipated availability or magnitude of a reward provided in the context of a behavioral task [3]. Indeed, several recent studies from Hikosaka's research group have indicated that caudate activity that anticipates a memory-guided saccade is sensitive to the contingency between the visual cue and the reward [6,7]. They designed the BST to address how this reward-related activity might be used in the process of generating the saccade.…”
mentioning
confidence: 99%
“…Of the 41 neurons with anticipatory activity, 31 exhibited spatially selective reward anticipation during the BST. Of these 31, 22 were tested on the second task and most, but not all, [7] and a representation of color-reward contingencies [6]. Learning how these different properties are represented across the population of neurons in the caudate will be an essential step in understanding its role in using information related to reward to influence oculomotor behavior.…”
mentioning
confidence: 99%